Influence of green pepper extract on the physicochemical, antioxidant, and sensory properties of stirred yogurt - Elham Kovsari; Parisa Shavali Gilani; Samira Shokri; Abdolreza Mircholi Borazgh; Alieh Rezagholizade-Shirvan; Ahmad Pedram Nia (Food Chemistry: X, 2024)
The green pepper has garnered interest in different societies as a functional food and food additive. Numerous studies have indicated that the phytochemicals found in pepper possess antioxidant, anti-cancer, anti-inflammatory, anti-obesity, and anti-arteriosclerotic properties. In this study, green pepper extract was used in yogurt to increase the acceptability of consumption and improve its health properties. For this purpose, green pepper extract was added in concentrations 100, 200, and 300 ppm in the preparation of yogurt. And pH, acidity, total content of phenolic compounds, DPPH inhibition percentage, viscosity, syneresis, and sensory properties were evaluated in 1, 7, 14, and 21 days after production. The results showed that by increasing the amount of extract, the percentage of antioxidant activity and phenolic compounds increased significantly. The effect of storage time on these indicators was also significant (p < 0.05). in such a way that over time, there was a decrease in antioxidant activity. But, there was a slight increase in antioxidant activity on the 14th day of storage. Also, the effect of treatment type on some physicochemical characteristics of yogurt containing green pepper extract including pH, acidity, viscosity, and syneresis was significant (p < 0.05). During storage, acidity, syneresis, and viscosity increased and pH decreased significantly in all yogurt samples. Regarding the tested sensory attributes, the 200 ppm sample received the highest score among the evaluators, and in terms of overall acceptance, the samples containing the extract were more favorable than the control sample.